2009
DOI: 10.1111/j.1744-313x.2009.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in CXCL12 and risk of cervical carcinoma: a population‐based case–control study

Abstract: SummaryCXCL12 provides a chemotactic signal directing leukocyte migration and regulates metastatic behavior of tumor cells. We conducted a population-based case-control study to test the hypothesis that common genetic variation in CXCL12 (single SNP alleles and haplotypes) is associated with the risk of cervical carcinoma. Cases (N=917) were women diagnosed with invasive squamous cell cervical carcinoma (SCC), adenocarcinoma or adenosquamous carcinoma or adenocarcinoma in situ (ACIS) of the cervix, while resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(94 reference statements)
1
17
0
Order By: Relevance
“…In the present study, the SDF1-3' G801A SNP was not identified as a risk factor for cervical cancer. The present observations are in agreement with those by Maley et al (23) and Tee et al (24), which also observed no association between the SDF1-3' G801A polymorphism and risk of cervical cancer. However, in the present study, the P-value assessment of the trend observed for the SDF1-3' G801A polymorphism was on the borderline of statistical significance.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, the SDF1-3' G801A SNP was not identified as a risk factor for cervical cancer. The present observations are in agreement with those by Maley et al (23) and Tee et al (24), which also observed no association between the SDF1-3' G801A polymorphism and risk of cervical cancer. However, in the present study, the P-value assessment of the trend observed for the SDF1-3' G801A polymorphism was on the borderline of statistical significance.…”
Section: Discussionsupporting
confidence: 94%
“…The possible role of the SDF1-3' A variant in the increased levels of transcription and protein has been reported (22). Certain studies have demonstrated no association between the SDF1-3' G801A single nucleotide polymorphism (SNP) and cervical carcinoma (23,24), however, the interaction between the SDF1-3' G801A SNP with other known risk factors of cervical cancer remain to be fully elucidated. In the present study, the SDF1-3' G801A genotype and allele frequencies were investigated in patients with cervical cancer (n=462) and healthy controls (n=497) in the Polish population, stratified based on contraceptive use, menopausal status, parity and history of tobacco smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Upon reviewing the abstracts, 10 articles were excluded since they were not case-control studies. After further examination of articles on full-text basis, 10 papers were excluded for P<0.05 in control HWE test [18][19][20][21] or failing to provide sufficient genotype data [22][23][24][25][26][27] . As a result, a total of 29 papers were included.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Previous studies have shown single nucleotide polymorphisms (SNPs) in the human SDF-1 gene may influence SDF-1 function, such as serum SDF-1 level (11,12) and its expression in hematopoietic stem cells in peripheral blood (13,14). These SNPs have also shown to be associated with malignant diseases such as cervical cancer (15), in which SDF-1 was believed to affect the metastatic behavior of the cancer cell. In SLE (16), T-cell function and survival are suggested to be affected by SDF-1 polymorphism.…”
mentioning
confidence: 99%